2014
DOI: 10.1038/ejcn.2014.89
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical analysis of dietary, lifestyle and family environment risk factors for childhood obesity: the GRECO study

Abstract: These findings could guide future investigations or public health initiatives to prevent and confront the childhood OB epidemic more efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 35 publications
6
41
3
1
Order By: Relevance
“…Although previous studies have reported the association between lifestyle factors (diet, physical activity habits and sedentary behaviors) and overweight/obesity among adolescents [24,30,31], these lifestyle factors were related to distorted body image independently of actual BMI in this study. Moreover, the impact of lifestyle on overestimating body weight varied by sex; overestimated body weight was positively associated with snacking after dinner among girls, while it was negatively associated with exercise behavior among boys.…”
Section: Discussioncontrasting
confidence: 81%
“…Although previous studies have reported the association between lifestyle factors (diet, physical activity habits and sedentary behaviors) and overweight/obesity among adolescents [24,30,31], these lifestyle factors were related to distorted body image independently of actual BMI in this study. Moreover, the impact of lifestyle on overestimating body weight varied by sex; overestimated body weight was positively associated with snacking after dinner among girls, while it was negatively associated with exercise behavior among boys.…”
Section: Discussioncontrasting
confidence: 81%
“…Eating fewer meals together as a family were associated with childhood obesity . Watching television while eating was also associated with increased risk , with a potential dose‐dependent relationship .…”
Section: Resultsmentioning
confidence: 98%
“…Obesity in both parents was identified as a risk factor for childhood obesity in nine studies whereas seven studies found that obesity in either parent was a risk factor . In terms of paternal weight, five studies reported associations between paternal BMI and childhood obesity, and 16 studies found associations between paternal and childhood obesity. Regarding pre‐partum maternal weight, three studies found relationships between BMI and childhood obesity, and seven studies reported associations between maternal obesity and childhood obesity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the two patterns characterized mainly by higher daily number of meals and snacks (component 3) and higher breakfast frequency (component 4) showed a negative association with free sugars intake. Previous work in this area has shown that both frequent breakfast consumption and a higher number of meals during the day, besides protecting against childhood OW/OB, are also associated with better diet quality (54)(55)(56)(57) . The limitations of the present work are mostly due to its cross-sectional nature since cause-and-effect relationships cannot be drawn.…”
Section: Discussionmentioning
confidence: 99%